ميتافيزيقية عما نوئيل كانط وموقف الفلسفة الاسلامية منها - توفيق, ضياء حبيب (Sulaimani Journal for Humanities, 2021)
The controversy among philosophers long ago, is the extent to which the external reality of mental reality. This philosophic question was inherited by the later philosophic epochs until it reached the modern age. Modernist philosophers tried to find suitable solutions for them, kant went beyond the method used to solve philosophical questions in ancient ways, macans criticism of the minds of his time began with philosophical ideas, especially Descartes who felt that critique of knowledge begins with absolute doubt, Kant not only critical ideas, but find him the basis for a new reading that differs from previous reading in solving the question that occupied the minds of philosophers of old, but despite his many attempts, he did not receive widespread acceptance, especially in his contemporaries and also in Islamic philosophy, so we find the latter stood up against Kants philosophical ideas, including the study of metaphysics for the observations of the failures of methodology and objectivity and its relationship to mental reality .